PRAGMATIC ASPECT IN THE TRANSLATION OF ANTONYMS IN ENGLISH AND UZBEK LITERATURE - Azimova Shahzoda Azim qizi (Bright Mind Publishing, 2025)
Translation is not a mere process of word-for-word substitution; it involves a complex interplay between linguistic, cultural, and pragmatic aspects. One of the most subtle and significant challenges in translation is the correct rendering of antonyms, especially between languages of different typological backgrounds, such as English and Uzbek. This article explores the pragmatic aspects of translating antonyms in English and Uzbek literature. It highlights the cultural, contextual, and stylistic nuances that influence how oppositional meanings are conveyed in two languages. The study draws on examples from well-known literary texts and offers insights into how translators navigate the pragmatic intricacies of antonymy to preserve authorial intent, emotional tone, and communicative impact.
Keywords: Pragmatics, antonyms, translation, English literature, Uzbek literature, semantic opposition, context, equivalence.